History matters in microfinance - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2003)
Microfinance is not a recent development, and neither is the development of regulation and supervision of microfinance institutions (MFIs). Every now developed country has its own history of microfinance. It is important to recognize this because it presents a view different from that of many in the microfinance community who associate microfinance with credit NGOs and believe that microfinance was invented in Bangladesh some 20-odd years ago. Attributing the origin of microfinance to recent initiatives misses not only the historical depth and scale of microfinance, but also centuries of experience, which means: learning from trial and error, failure and success. The beginnings in Europe were all informal and small-scale, including informal savings clubs, among them the box clubs in England during the 18th century.
Keywords: 330; Mikrofinanzierung; Geschichte; Informeller Finanzsektor; Kreditgenossenschaft; Irland; Deutschland; Welt